Poetry Appreciation and Paraphrasing Skills of Grade 9 Students - Jane Catherine A. Tobis; Chona G. Mascuñana (Philippine Social Science Journal, 2020)
Among all the literary pieces used in English language teaching, poetry has always been regarded as an interesting and challenging literature genre used in English language teaching. Researchers that explored the appreciation of poetry and the factors that affect its approach had different points of view; however, they certainly agreed on the universal concern of research on the difficulty and lack of enthusiasm in dealing with poetry. Accordingly, recent neuroscientific research commenced using poetry in paraphrasing since both complement one another in language teaching. As a literary product, poetry requires a high analysis skill for adequate comprehension, while paraphrasing involves extensively analyzing ideas and forming new borrowed personal interpretation. Hence, this study aimed to see the relationship between students' degree of poetry appreciation and paraphrasing skills.